A Study on the Intelligence Profiles of Taiwan Indigenous Students: The Case of Second Grade Pupils - Liu, Wei-Yu; Teele, Sue (The Australian Journal of Indigenous Education, 2009)
Abstract This paper attempts to develop an intelligence-fair assessment tool to explore the intelligence profiles of 15 second grade Amis pupils. This study was conducted in an elementary school in Taiwan with a largely Amis population of lower socioeconomic status. The results illustrate that the most developed intelligence for eight pupils was musical intelligence and that most pupils in this class are also skilled at bodily-kinesthetic and linguistic intelligence. However, these second grade pupils did not have very highly developed interpersonal intelligences which traditionally stereotyped the capabilities of indigenous pupils. Furthermore, each student had his/her own unique intelligence profile. Do Amis pupils have a particular intelligence profile as a group? Or are their individual differences greater than their group similarities? It is recommended that future studies observe both the whole ethnic group and individual pupil's intelligence profile to help each pupil develop to their full potential.